The long-term consequences of debt issuance. - Lesseig, Vance P. (My University, 1999)
In addition, the equity returns of debt issuers are significantly lower than those of non-issuing firms. The duration of the underperformance rivals that of new equity issuers although the magnitude is much less than that reported in studies of equity issuance. The magnitude of underperformance becomes larger when book-to-market value is used as a matching criterion.

Recently, the long-term common stock performance of equity issuers has been examined with surprising results. Equity issuers, making either new or seasoned offers, earn significantly smaller returns compared to non-issuers for up to five years following the issue. This work addresses the long-term impact on investors of firms that choose to issue debt. Both the equity returns of the debt issuer as well as the returns of the new debt issue itself are examined. The results indicate that the securities of new debt issuers are not good investments. Both the stock of the debt issuer as well as the new debt itself fail to provide returns as high as their matched counterparts over periods up to five years after issuance. The returns on the new debt are significantly lower than those of existing debt even after careful matching on various debt characteristics. The duration and magnitude of the underperformance is related to the credit quality of the issue, and appears to be only partially explained by the new issue's liquidity.
Keywords: Economics, Finance.; Debt financing (Corporations)